PROFIL KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK SMA DI KOTA SUKABUMI - Rizki Annur Tri Septiani; Suhendar Suhendar; Billyardi Ramdhan (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2020)
The problem-solving ability of students at a senior high school (SMA/MA) level is the competencies that must be possessed at school and outside school. This study aimed to look at the profile of the problem-solving ability of class XI students’ in the Senior High School of Sukabumi. The method used was a quantitative descriptive method. The subjects of this study were 36 students of class XI in the Senior High School of Sukabumi. The sampling technique used was a purposive sampling technique. Environmental change material is a biology subject in class X. It has been stated in the curriculum of 2013 that gives guidance to students to be able to solve the problem in every biology subject materials. The instrument used was in the form of an essay of 10 questions with the reliability of 0,82, deviation standard of 7,78, and correlation of 0,69. These questions using 5 indicators of problem-solving ability. The results of this study have the following percentage: formulating the problem was 68.75%, developing temporary answers was 68, 4%, testing the interim answers was 77.43%, concluding was 67.01%, and applying conclusions was 51.04%. The results of the study showed that the problem-solving abilities of class XI students of Sukabumi High School in enough category with an average percentage of 66.52%. It can be concluded that students' problem-solving abilities still need to be improved. The teachers should improve the learning model, media, and learning environment as it can enhance student’s problem-solving ability. Further research is very needed to be done to add insight knowledge.